A tecnologia e a informação na construção de valores de responsabilidade social - Dantas, Willy de Macedo [UNESP] (2006)
In the last decades the technology has been incorporated to the way reality to reconfigure the current scene all, bringing I obtain deep transformations that excessively impact in all the fields of the human knowledge and in the social behavior. In the information the impacts have been right-handers, leading in consideration the concurrence of the technology process to the informational explosion and its applicability in the organizational environment. In this direction, it appears as problem the impact that the allied technology to the information has on the construction of social values of the culture of an organization. This work searchs to understand the way as the technology and the information comes working in its dissemination and, in this way, to construct the values that are make a speeched for the socially responsible organizations, ahead of the reality of the new context of the revolution of the TIC's -Technologies of the Information and Communication. The work follows as north axles of quarrel and study, being: technology -information -organizational culture and social responsibility. In intention to organize the search for this knowledge, they are made use of the comparative method to form the scene of the socially responsible organizations, using itself of two instruments of collection of data, the interview and the questionnaire. Through the collected data, understanding of the reality of the organizations is looked to arrive á, analyzing the scene of the technology and information and its paper in way the construction of the organizational culture, having for base the relevance that both possess for the process of the dissemination of the values of the Social Responsibility for its incorporation in the internal public of the organizations.